Probability and statistical inference - Hogg, Robert V.; Tanis, Elliot A.; Zimmerman, Dale L. (Pearson Education, 2015)
This applied introduction to probability and statistics emphasizes the existence of variation in almost every process, and how the study of probability and statistics helps us understand this variation. Designed for students with a background in calculus, this book continues to reinforce basic mathematical concepts with numerous real-world examples and applications to illustrate the relevance of key concepts.